INTEGRASI GREEN LEADERSHIP DAN GREEN HUMAN RESOURCE MANAGEMENT: STRATEGI MENCAPAI KEBERLANJUTAN ORGANISASI DI ERA BISNIS MODERN - R. Setya Saga Perwira; Tri Siwi Agustina; Dian Ekowati; Widyantari Dwipa (TECHNOBIZ : International Journal of Business, 2025)
The objective of this study is to examine the integration of green leadership and green human resource management (GHRM) as a strategic approach to achieving organizational sustainability in the modern business era. This research employs a Systematic Literature Review (SLR) based on the PRISMA protocol, analyzing seven peer-reviewed journal articles published between 2022 and 2024. The findings indicate that green leadership, with its visionary, transformational, and participative dimensions, plays a vital role in embedding sustainability values into organizational culture and influencing employees’ pro-environmental behavior. Meanwhile, GHRM contributes through practices such as green recruitment, green training, and performance appraisal, which serve as operational instruments to institutionalize sustainability through the development of green human capital. The integration of these two approaches creates strategic synergy that enhances green innovation, supply chain sustainability, and organizational competitiveness. This study contributes conceptually by mapping the relationship between leadership and human resource management in building sustainable organizations and offers practical insights for policy and managerial development. The limitation of this study lies in its reliance on secondary data sources. Future research is recommended to adopt empirical approaches across broader industrial and geographical contexts.